If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -5(8 + -4x) = -1 + -4x 3 + (8 * -5 + -4x * -5) = -1 + -4x 3 + (-40 + 20x) = -1 + -4x Combine like terms: 3 + -40 = -37 -37 + 20x = -1 + -4x Solving -37 + 20x = -1 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -37 + 20x + 4x = -1 + -4x + 4x Combine like terms: 20x + 4x = 24x -37 + 24x = -1 + -4x + 4x Combine like terms: -4x + 4x = 0 -37 + 24x = -1 + 0 -37 + 24x = -1 Add '37' to each side of the equation. -37 + 37 + 24x = -1 + 37 Combine like terms: -37 + 37 = 0 0 + 24x = -1 + 37 24x = -1 + 37 Combine like terms: -1 + 37 = 36 24x = 36 Divide each side by '24'. x = 1.5 Simplifying x = 1.5
| 5(2x-2)-3x=-2(3x-8) | | -0.40x+8=0.50x | | 0.33x+1=9 | | -5(x-3)=15(x-7)+2 | | 1.75x=8 | | 5-(x-3)=6-2x | | 5-x=4x-60 | | 7x-2x=8-3x | | 3x+8=-4x+8 | | -4x-1=-1+7x | | 4x-12=-7x+10 | | 5x-x=3x-2 | | -x+3=23 | | -2x-6=16 | | x^3-12= | | 7x-(3x+6)=5x-47 | | 5x^2+1=2x | | 2y^3-7y^2+3=0 | | 50x^2+1=2x | | 6x-7x-5=0 | | 16x-282=6x-12 | | 52-6x=12x+18 | | 9x-(7x+2)=3x-22 | | 6x+22=16x-98 | | 3x^2+2x-40=0 | | 3x^2+58x-40=0 | | 3x^2+119x-40=0 | | x^2+25x-24=0 | | 2x+125=6x+93 | | (x)(x+1)(x+2)=720 | | 2x+25=6x+93 | | 3x^2-29x-10=0 |